Targeting nNOS ameliorates the severe neuropathic pain due to chronic pancreatitis - Demir, Ihsan Ekin; Heinrich, Tobias; Carty, Dominique G.; Saricaoglu, Ömer Cemil; Klauss, Sarah; Teller, Steffen; Kehl, Timo; Mota Reyes, Carmen; Tieftrunk, Elke; Lazarou, Maria; Bahceci, Dorukhan H.; Gökcek, Betül; et al. (EBioMedicine, 2019)
Background: Pain due to pancreatic cancer/PCa or chronic pancreatitis/CP, is notoriously resistant to the strongest pain medications. Here, we aimed at deciphering the specific molecular mediators of pain at surgical-stage pancreatic disease and to discover novel translational targets. Methods: We performed a systematic, quantitative analysis of the neurotransmitter/neuroenzmye profile within intrapancreatic nerves of CP and PCa patients. Ex vivo neuronal cultures treated with human pancreatic extracts, conditional genetically engineered knockout mouse models of PCa and CP, and the cerulein-induced CP model were employed to explore the therapeutic potential of the identified targets. Findings: We identified a unique enrichment of neuronal nitric-oxide-synthase (nNOS) in the pancreatic nerves of CP patients with increasing pain severity. Employment of ex vivo neuronal cultures treated with pancreatic tissue extracts of CP patients, and brain-derived-neurotrophic-factor-deficient (BDNF+/−) mice revealed neuronal enrichment of nNOS to be a consequence of BDNF loss in the progressively destroyed pancreatic tissue. Mechanistically, nNOS upregulation in sensory neurons was induced by tryptase secreted from perineural mast cells. In a head-to-head comparison of several genetically induced, painless mouse models of PCa (KPC, KC mice) or CP (Ptf1a-Cre;Atg5fl/fl) against the hypersecretion/cerulein-induced, painful CP mouse model, we show that a similar nNOS enrichment is present in the painful cerulein-CP model, but absent in painless genetic models. Consequently, mice afflicted with painful cerulein-induced CP could be significantly relieved upon treatment with the specific nNOS inhibitor NPLA. Interpretation: We propose nNOS inhibition as a novel strategy to treat the unbearable pain in CP. Fund: Deutsche Forschungsgemeinschaft/DFG (DE2428/3-1 and 3-2).
CRIS-Team Scopus Importer:2019-08-13
Keywords: Atg5; Chronic pancreatitis; Genetically engineered mice; Neurology of the digestive tract; Nitrergic; nNOS; Pain; Pancreatic cancer